Extending the INWA Grid - Lloyd, Ashley; Sloan, T. (ESRC National Centre for e-Social Science, 2005)
The INWA project (Innovation Node: Western Australia) has previously investigated and reported on the use of existing Grid technologies for secure data mining of corporate data and the use of that data to build predictive models of consumer behaviour. The INWA grid infrastructure between the UK and Australia that was built and utilized during these investigations has recently been extended to include China. This paper introduces the INWA project, describes its technical grid infrastructure and reviews challenges encountered when upgrading the grid infrastructure and extending it to China.